A Mixed Methods Approach to Tailoring Evidence-Based Guidance for Antibiotic Stewardship to One Medical System. Issue 1 (June 2018) - Patterson, Emily S.; Dewart, Courtney M.; Stevenson, Kurt; Mbodj, Awa; Lustberg, Mark; Hade, Erinn M.; Hebert, Courtney
Our objective is to operationalize a novel antibiotic advisor, called the personalized weighted incidence syndromic combination antibiogram (pWISCA), intended to help physicians with initial antibiotic choice in hospitals. Clinical decision support tools are a promising technology for providing evidence-based guidance that incorporates data about patients from electronic health records. Nevertheless, congruence with policies and procedures and local experts' opinions, as well as taking into account local resistance data for the medical center's patient population, is needed when selecting and ordering the antibiotic medication options provided by pWISCA. This paper presents findings from applying a mixed methods approach to identify and prioritize antibiotic medications and associated contextual data to display in a CDS tailored to the local hospital. We discuss implications of these findings.